Effeminacy among university students: exploring the perception towards effeminacy from university students' perspectives / Khadijah Said Hashim ... [ et al. ] - Hashim, Khadijah Said; Maaruf, Siti Zuraida; Azizan, Intan Syahriza (2009)
The concern of this research is to explore the students' perception towards the issue of effeminacy in higher institution. It is assumed that, different people will hold different perception towards this group. On top of that, to define effeminacy it is a phenomenon when a male has a tendency to exhibit and adopt one or more of female character (s) and behavior. The study is relevant because despite rejection, stigma and negative treatment from society, effeminacy still exist and increase in number. In the effort to explore about students' perception towards effeminacy, this research focuses on research question: perception on effeminates social relationship and friendship. The survey conducted by distributing questionnaires to 100 respondent students ranging from 19 years old to 36 years old of males and females. The data reveals that majority of the respondents (91%) have effeminate friends and the remaining of 9% have no experience any friendship with effeminates. It is hoped that, this research will at least give a better insight to the society at large, about effeminates as one of the groups that exist in society before giving any stereotypical remarks. In fact, this group and other similar groups like transvestites and hermaphrodites should not be discriminated blindly as they need help, guide and support to continue their lives and functions in society.